college algebra

posted by .

explain why (x + y)2= x2 + y2

  • college algebra -

    If you are telling me that
    (x+y)^2 = x^2 + y^2
    That is not true
    (x+y)^2 = x^2 + 2 x y + y^2
    as you can see by multiplying
    (x+y)(x+y) = x(x+y) + y(x+y) =x^2 + xy + xy + y^2

  • college algebra -

    Now if you mean
    2 (x + y) = 2 x + 2 y
    that is simply the distributive property of multipication.

  • college algebra -

    solc for v


Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. College Algebra

    Can some please help me and explain this problem to me! Or if you know of any website that will help! Thanks. -2x+4>12
  2. College Algebra

    Solve 2x(squared)-3x-2=0 using the quadratic formula. Can someone explain this to me please?
  3. college algebra

    The graph of a power function is f(x)=kx^p, where k and p are constants. Do you expect k to be positive or negative ?
  4. college level algebra

    I need to explain why subtracting a negative is like adding
  5. college algebra

    Explain how to identify intervals on which a function increases, decreases, or is constant.
  6. College Algebra

    Solve the following equation in the complex number system x^4+x^3+4x^2+10x-60=0 College Algebra - Reiny, Monday, January 2, 2012 at 11:49pm hint x = 2 and x = -3 are roots so either do long division by x-2 and x+3 to get a quadratic …
  7. statistics

    At a small college it is known from previous years that 35% of all college freshman start in college algebra. The new freshman class has 100 students in it, What is the probability that between 35 and 42 freshman will start in college …
  8. college algebra

    I you are given two real numbers, explain how to determine which one is lesser.
  9. economic

    College enrollments increased at the same time that average tuition rose dramatically. Does this contradict the law of downward-sloping demand?
  10. College Algebra

    Use the definition of the logarithmic function to find x. (a) ln x = 6 x = (b) ln e^2 = x x = can someone explain to me how to do this?

More Similar Questions